PRODUCTION OF RED-COLORED RICE FLOUR THROUGH IMPREGNATION WITH RED PITAYA EXTRACT DURING SOAKING AND MILLING - Gunarso, Amelia Agatha; Sofia Murtini, Erni; Harijono (Fakultas Teknologi Pertanian Universitas Brawijaya, 2025)
Rice flour is a common ingredient in traditional food processing in Indonesia. Rice flour is commercially found in the market as white rice flour, and colorants are often added during processing. Traditionally, natural colorants are derived from plant sources, such as red pitaya (dragon fruit). Red pitaya is usually extracted and added separately to the dough. However, this practice is considered inefficient. Therefore, this study aimed to explore the impregnation of red pitaya’s pigments into rice flour and develop red-colored rice flour. Impregnation was carried out during the processing of rice grain into rice flour, specifically during soaking and milling, with varying soaking times (4, 8, and 12 hours). The results showed that pigment impregnation during soaking produced the best red-colored rice flour after soaking in the extract for 8 hours, with a moisture content of 10.9%; starch content of 68.5%; water-binding capacity of 232.14%; oil-binding capacity of 202.27%; and a particle size of 55.18 mm. Pigment impregnation during milling produced the best red-colored rice flour after 4 hours of soaking, with a moisture content of 12.3%, starch content of 76.6%, water-binding capacity of 206.45%, oil-binding capacity of 213.98%, and a particle size of 55.51 mm. The application of red-colored rice flour to rice paper shows that impregnation during soaking has a higher level of consumers’ acceptability, with a pink color and chewy texture, while impregnation during milling has a whiter color and a stiff texture of rice paper.